Behavioural Response Patterns on the Government Incentives Influencing Compliance Behaviour of Business Zakat among SMEs - Kamarudin, Mohd Faizal; Khamis, Mohd Rahim; Rahman, Azman Abd (Advances in Social Sciences Research Journal, 2023)
Government incentives and compliance behaviour of business zakat have a significant relationship as revealed by a few studies. However, the lack of study focused on respondents' response on the government incentives in influencing compliance behaviour of business zakat. Hence, this article examines the usage of Rasch Wright map in evaluating the behavioural response patterns on the government incentives and compliance behaviour of business zakat among SMEs. A total of 276 questionnaires were collected from SMEs entrepreneurs in Selangor. The Rasch Measurement Model was employed to analyze the data. Out of the 276 questionnaires collected, only 247 responses were consistent with the Rasch Measurement Model. Among the respondents, 107 individuals (43.3%) who complied with business zakat payment were influenced by government incentives, while 140 individuals (56.7%) who did not comply with business zakat payment were likely not influenced by government incentives. This study's results highlight the importance of the Rasch Measurement Model in elucidating the response patterns of participants, demonstrating its ability to explain how government incentives impact compliance behavior regarding business zakat among SMEs. This study has illustrated that this method of analysis is expedient in identifying the unusual and inappropriate response patterns and items based on fit statistics and misfit response series compared others. This shows that the Rasch Measurement analysis is an alternative tool to investigate the behavioural response patterns since analyze items and respondents of the study. This study suggests that future research regarding compliance and zakat employ the Rasch Measurement Model analysis as an alternative method to identify ability of respondents and the response behavior patterns among respondents.